Effects of 17β-estradiol on the cytoarchitecture of pyramidal CA1 neurons in normoglycemic and diabetic male spontaneously hypertensive rats - Brocca, María Elvira (2014)
Previous work has shown a reduction of apical dendritic length and spine density in neurons from the CA1 hippocampus subfield of spontaneously hypertensive rats (SHR). These abnormalities are prevented by treatment for 2 weeks with 17 beta-estradiol. In view of the fact that diabetes and hypertension are comorbid diseases, we have now studied the effect of Streptozotocin-induced diabetes on the dendritic tree and spines of CA1 hippocampus neurons, and also compared the regulation of these parameters by 17 beta-estradiol in diabetic and normoglycemic SHR. Twenty week old male SHR received iv 40 mg/kg Streptozotocin or vehicle and studied one month afterwards. A group of normoglycemic and hyperglycemic SHR also received sc a single 17 beta-estradiol pellet or vehicle for 2 weeks. Hippocampus sections were impregnated with silver nitrate following a modified Golgi´s method and the arbor of CA1 pyramidal neurons analyzed by the Sholl´s method. 17 betaestradiol treatment of normoglycemic SHR reversed the reduced length of apical dendrites, the low spine density and additionally decreased blood pressure. Diabetic SHR showed increased length of apical and basal dendrites but reduced spine density compared to normoglycemic SHR. Diabetes also decreased blood pressure of SHR. Treatment with 17 beta-estradiol of diabetic SHR enhanced dendritic length, increased dendritic spine density and further decreased blood pressure. Thus, changes of cytoarchitecture of CA1 neurons due to 17 beta-estradiol treatment of normoglycemic SHR persisted after diabetes induction. A decrease of blood pressure may also contribute to the central effects of 17beta-estradiol in SHR diabetic rats.